Effect of atrazine and zearalenone on the numer of receptor binding sites for 3H-estradiol in the rat uterus cytosol - M. Mitak; T. Gojmerac; D. Cvrtila; Ž. Cvetnič (Veterinární Medicína, 2002)
The effect of a daily dose of 14 mg atrazine and/or 2.5 mg zearalenone that were administered to rats during 5 days of estrous cycle on the number of receptor binding sites for 3H-estradiol in uterine cytosol was investigated. Comparison with a control group of animals showed no effect of atrazine influence on the number of receptor binding sites for 3H-estradiol in the rat uterine cytosol until day 6 of the experiment, when a significantly lower value was recorded (P < 0.05). In the group of animals administered zearalenone, a decline in the number of receptor binding sites for 3H-estradiol in uterine cytosol was observed. On day 4 of the experiment, the number of binding sites was significantly greater (P < 0.05) in this group than in the control group of animals, whereafter it gradually decreased to a significantly lower value (P < 0.05) as compared to the control group on day 6. In the group of animals administered a mixture of atrazine and zearalenone, the number of receptor binding sites for 3H-estradiol in uterine cytosol did not decrease but showed a similar pattern as in the control group of animals, however, at a statistically significantly (P < 0.05) higher level.